UNDERSTANDING OFFLINE PRO-ENVIRONMENTAL IDENTITY: FACTORS AND IMPLICATIONS - Tusyanah, Tusyanah; Haryanti, Rahayu Puji; Sakitri, Wijang; Ismiyati, Ismiyati; Chayati, Nur (Journal of Environmental Science and Sustainable Development, 2025)
Given global environmental challenges, developing sustainable behavior among pre-service teachers is crucial, as they will be responsible to educate future generations who must contribute to solving environmental problems. Offline pro-environmental identity refers as the individual's environmental commitment in real-life setting. Previous studies have primarily focused on online identity and behavioral intentions, while real-life behavioral context have not been fully examined. The goal of this study was to investigate the effects of the online pro-environmental identity, the perceived behavioral control, and the moral identity on the behavioral intention and the offline pro-environmental behavior. The study employed a quantitative research design and adopted Covariance-Based Structural Equation Modeling (CB-SEM) to analyze the data. The population was all Economics Education students of Universitas Negeri Semarang. A proportionate simple random sampling method was employed to choose 277 respondents. Questionnaire-based data were obtained and analyzed using CB-SEM. The findings reveal that intention was a strong and positive predictor of offline pro-environmental behavior (H1). Moral identity significantly influences intention (H2) and affects offline behavior both directly (H3) and indirectly through intention (H8). Online pro-environmental identity also has a significant influence on both intention (H4) and offline behavior (H5), with both effects mediated by intention (H9). However, perceived behavioral control has no impact on either intention (H6) or discharge behavior offline (H7), even indirectly through intention (H10). R value for intention is a moderate 0.539 whereas offline pro-environmental behaviour shows a strong R value at 0.963. These results emphasize the importance of intention for transforming values and identity to actual ecological behaviour. Enhancing moral and online pro-environmental identity can be beneficial to the development of sustainable behavior in offline context which calls for joint efforts in environmental education and behavioral interventions.